Rise of Digital Marketing and Its Impact in Logistics & Supply Chain - Mitul, Aklima Rahman (Brac University, 2021)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2020.